2016
DOI: 10.1080/14767058.2016.1219717
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum ADAMTS-9 levels in gestational diabetes: a pilot study

Abstract: ADAMTS-9 levels were significantly lower in GDM pregnancies. This may help to understand the mechanism of GDM pathogenesis. In future, target treatments with ADAMTS proteins may help to improve the severity of diabetes pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In a previous report, Santiago et al [128], Auburger et al [129], Qu et al [130], Ś et al [131] and Hjortebjerg et al [132] reported that SLC22A5, SH2B3, ITPR3, CALD1 and IGFBP4 expression might be regarded as an indicator of susceptibility to type 1 diabetes mellitus, but these genes might be associated with progression of GDM. Krishnan et al [133], Hu et al [134], Martins et al [135], Prieto-Sánchez et al [136], Sugulle et al [137], Zhao et al [138], Siddiqui et al [139], Han et al [140], Lappas et al [141], Wang et al [142], Artunc-Ulkumen et al [143], Blois et al [144], Vacínová et al [145] and Vilmi-Kerälä et al [146] demonstrated that the expression of CREBRF (CREB3 regulatory factor), STRA6, EGFR (epidermal growth factor receptor), MFSD2A, GDF15, PAK1, VCAM1, IGFBP2, IGFBP7, PRKCA (protein kinase C alpha), ADAMTS9, LGALS1, BIN1, TIMP1 and are associated with progression of GDM. Aquila et al, [147],Chen et al [148], Xie et al [149], Zhang et al [150], Aspit et al [151], Akadam-Teker et al [152], Jiang et al [153], Cetinkaya et al [154], Grond-Ginsbach et al [155], Dong et al [156], Chardon et al [157], Chen et al [158], Yamada et al [159], Hu et al [160], Bobik and Kalinina [161], Schwanekamp et al [162], Liu et al [163], Schroer et al [164], Raza et al [165], Yang et al [166], Azuaje et al [167], Durbin et al [168], Chowdhury et al [169], Wang et al [170], Li et al [171], Lv et al [172], Bertoli-Avella et al [173], Grossman et al [174], Andenæs et al [175] and Chen et al [176] demonstrated that HES1, SPIN1, TBX3, EVA1A, CAP2, BMP1, HSPB8, RDX (radixin), COL5A1, LIMS2, PARVA (parvin alpha), EGFLAM (EGF like, fibronectin type III and laminin G domains), NEXN (nexilin F-actin binding protein), TNFRSF14, TGFBI (transforming growth factor beta induced), HAVCR2, CDH11, COL4A1, COL4A2, COL5A2, SHROOM3, HYAL2, PDLIM3, ETS2, PLSCR4, TGFB3, COL6A2 and LTBP2 could induce cardiovascular diseases, but these genes might be essential for progression of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, Santiago et al [128], Auburger et al [129], Qu et al [130], Ś et al [131] and Hjortebjerg et al [132] reported that SLC22A5, SH2B3, ITPR3, CALD1 and IGFBP4 expression might be regarded as an indicator of susceptibility to type 1 diabetes mellitus, but these genes might be associated with progression of GDM. Krishnan et al [133], Hu et al [134], Martins et al [135], Prieto-Sánchez et al [136], Sugulle et al [137], Zhao et al [138], Siddiqui et al [139], Han et al [140], Lappas et al [141], Wang et al [142], Artunc-Ulkumen et al [143], Blois et al [144], Vacínová et al [145] and Vilmi-Kerälä et al [146] demonstrated that the expression of CREBRF (CREB3 regulatory factor), STRA6, EGFR (epidermal growth factor receptor), MFSD2A, GDF15, PAK1, VCAM1, IGFBP2, IGFBP7, PRKCA (protein kinase C alpha), ADAMTS9, LGALS1, BIN1, TIMP1 and are associated with progression of GDM. Aquila et al, [147],Chen et al [148], Xie et al [149], Zhang et al [150], Aspit et al [151], Akadam-Teker et al [152], Jiang et al [153], Cetinkaya et al [154], Grond-Ginsbach et al [155], Dong et al [156], Chardon et al [157], Chen et al [158], Yamada et al [159], Hu et al [160], Bobik and Kalinina [161], Schwanekamp et al [162], Liu et al [163], Schroer et al [164], Raza et al [165], Yang et al [166], Azuaje et al [167], Durbin et al [168], Chowdhury et al [169], Wang et al [170], Li et al [171], Lv et al [172], Bertoli-Avella et al [173], Grossman et al [174], Andenæs et al [175] and Chen et al [176] demonstrated that HES1, SPIN1, TBX3, EVA1A, CAP2, BMP1, HSPB8, RDX (radixin), COL5A1, LIMS2, PARVA (parvin alpha), EGFLAM (EGF like, fibronectin type III and laminin G domains), NEXN (nexilin F-actin binding protein), TNFRSF14, TGFBI (transforming growth factor beta induced), HAVCR2, CDH11, COL4A1, COL4A2, COL5A2, SHROOM3, HYAL2, PDLIM3, ETS2, PLSCR4, TGFB3, COL6A2 and LTBP2 could induce cardiovascular diseases, but these genes might be essential for progression of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…conducted a pilot study evaluating serum levels of ADAMTS9 in patients with GDM. They demonstrated a significant reduction in serum ADAMTS9 levels in GDM patients and proposed that treatments targeting ADAMTS proteins may help to improve diabetes outcomes …”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated a significant reduction in serum ADAMTS9 levels in GDM patients and proposed that treatments targeting ADAMTS proteins may help to improve diabetes outcomes. 13 ADAMTS proteases and proteoglycans are widely expressed in fetal tissues and play an important role in numerous embryological developmental processes, including tissue remodeling, organogenesis, extracellular matrix remodeling and angiogenesis, as well as maternal processes such as cervical dilatation and post-partum uterine involution. 18 Beginning in the early stages of pregnancy, ADAMTS and extracellular matrix proteoglycans expressed in fetal membranes modify the intrauterine microenvironment, leading to insulin resistance in the second and third trimesters of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metalloproteinases serve essential roles in morphogenesis, tissue remodeling, and cell migration, all of which are important in normal or disease processes. From genome-wide association studies (GWAS), Adamts9 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 9) is associated with various human diseases, such as diabetes [1][2][3] , asthma [4] , arthritis [5,6] , artery calci cation [7,8] , macular degeneration [9], and cognitive aging [10] . However, Adamts9-dependent physiological processes, adamts9 expression, and in vivo functions are still poorly understood mainly due to the lack of non-lethal vertebrate knockout animal models.…”
Section: Introductionmentioning
confidence: 99%